Vision in the vertical axis: how important are visual cues in foraging and navigation? - Campbell, JL; Burt De Perera, T (SAGE Publications, 2023)
In both terrestrial and aquatic environments, a large number of animal behaviors rely on visual cues, with vision acting as the dominant sense for many fish. However, many other streams of information are available, and multiple cues may be incorporated simultaneously. Being free from the constraints of many of their terrestrial counterparts, fish have an expanded range of possible movements typified by a volume rather than an area. Cues such as hydrostatic pressure, which relates to navigation in a vertical plane, may provide more salient and reliable information to fish as they are not affected by poor light conditions or turbidity. Here, we tested banded tetra fish (Astyanax fasciatus) in a simple foraging task in order to determine whether visual cues would be prioritized over other salient information, most notably hydrostatic pressure gradients. We found that in both vertical and horizontal arrays there was no evidence for fish favoring one set of cues over the other, with subjects making choices at random once cues were placed into conflict. Visual cues remained as important in the vertical axis as they were in the horizontal axis.